Maize (Zea mays L.) and Sorghum (Sorghum bicolor L. Moench) Growers Knowledge, Perception and Management of S. frugiperda (Smith 1974) Attacks in the Sudano-Sahelian Zone of Mali - Konate, Modibo Amadou; Kouressy, Mamoutou; Teme, Niaba; Boukary, Ibrahim Baoua; Diaby, Mahamadou; Ndiaye, Mamadou; Dabo, Hamara; Diallo, Sory; Amadou, Laouali; Yaro, Alpha Seydou (European Journal of Applied Sciences, 2023)
Primary sector essentially dominates Malian economy which relies mainly on cereal crops. Among these cereals, maize and sorghum play a key role in human and animal nutrition. However, since 2017, in addition to other biotic and abiotic hazards, these two crops have been subjected to a new pest infestation, the fall armyworm (FAW). To determine growers’ level of knowledge and perception of FAW management practices, a survey was conducted in July 2021 in Ségou and Koutiala, regions, in Mali. The survey involved 201 maize and sorghum growers. Respondents were selected on the basis of whether they were maize or sorghum growers. The Kobocollect application was used for data collection. Survey results indicated that growers were aware of FAW pest four years ago in all surveyed villages in 2021. The survey revealed that 94.5% of growers knew how to identify FAW. For 34.2% of respondents, the FAW presents a great hazard to maize and sorghum crops in fields. Respondents (99.7%) perceived FAW as an economically detrimental hazard to the two crop yields. Results showed that 37.2% of respondents used no pesticides FAW management. Chemical methods were used by 17.6% of growers, compared to 4.3% for traditional methods. Preliminary results of this survey can be starting points to evaluate different biological control options to determine the best agro-ecological methods for controlling FAW on maize andsorghumcrops.